Errors in Import-Demand Estimates Based Upon Unit-Value Indexes - Shiells, Clinton R. (The Review of Economics and Statistics, 1991)
Disaggregated import-demand elasticity estimates based on import unit-value indexes are used in virtually all trade policy simulation models. However, unit-value indexes have been criticized especially by Irving B. Kravis and Robert E. Lipsey (1974). To examine the effect of using unit-value indexes on estimates of disaggregated import-demand elasticities, this paper compares regression results using unit-value indexes with results using U.S. Bureau of Labor Statistics import-price indexes for several detailed trade categories based on quarterly data for 1978-88. Results show that using unit-value indexes does not greatly affect estimated import-demand elasticities. Copyright 1991 by MIT Press.